2021
DOI: 10.47626/1679-4435-2021-580
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low back pain in Port of Santos workers

Abstract: INTRODUCTION: Low back pain is a common symptom among the general population and among manual workers, contributing to high rates of absenteeism and a decrease in overall quality of life. OBJECTIVES: To determine the prevalence of low back pain in Port of Santos workers, its influence on overall quality of life, physical activity level, and associated absenteeism rate. METHODS: This cross-sectional prevalence study was based on prospective da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(53 reference statements)
0
2
0
1
Order By: Relevance
“…Descriptive analysis was used to demonstrate basic characteristic of survey data in this study, among these participants, the jobs require a lot of physical labor only accounted for 11.9%~26.4%, which indicated that with equipment upgrading, numerous intelligent equipment and machines have replaced the simple, repetitive and strenuous physical jobs in the port, which reduces the physical dependence to a certain extent. Although the manual labor level has decreased, the level of mental labor has increased, therefore, the occupational stress and health problems according to mechanical vibration and noise, prolonged working posture and concentration, and other occupational hazards may gradually be more obvious 19 . The occupational disease spectrum of port employees may change because of the change of working practices, this change suggests that we should cause our attention Analysis result indicates that missing data were mainly concentrated in the physical examination dataset, such as motor and neurological function examination items, because these items were fill in the results by professional physicians after examining and diagnosing, if the result is normal (negative), leaving the item blank by default, and if the result is abnormal, the item will be fill in.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive analysis was used to demonstrate basic characteristic of survey data in this study, among these participants, the jobs require a lot of physical labor only accounted for 11.9%~26.4%, which indicated that with equipment upgrading, numerous intelligent equipment and machines have replaced the simple, repetitive and strenuous physical jobs in the port, which reduces the physical dependence to a certain extent. Although the manual labor level has decreased, the level of mental labor has increased, therefore, the occupational stress and health problems according to mechanical vibration and noise, prolonged working posture and concentration, and other occupational hazards may gradually be more obvious 19 . The occupational disease spectrum of port employees may change because of the change of working practices, this change suggests that we should cause our attention Analysis result indicates that missing data were mainly concentrated in the physical examination dataset, such as motor and neurological function examination items, because these items were fill in the results by professional physicians after examining and diagnosing, if the result is normal (negative), leaving the item blank by default, and if the result is abnormal, the item will be fill in.…”
Section: Discussionmentioning
confidence: 99%
“…У загальній популяції порівняно з професійними групами хворих було встановлено, що в обох групах дослідження у 25 % обстежених первинний біль у спині трансформувався в хронічний БНС. Наукові дослідження довели, що серед основних причин ризику розвитку первинного болю в спині посідає значна кількість фізичних (у тому числі виробничих) та психосоціальних факторів [12].…”
Section: проблемні теми Problematic Topicsunclassified
“…In a meta-analysis performed according to Systematic Reviews and Meta-Analyses, which included patients older than 18 years in 41 cohort studies, and researched risk factors for the development of LBP (lower back pain), which is the main manifestation of radiculopathy, in the general population compared to professional groups of patients, it was established that in both groups in 25 % of the examined primary back pain transformed into chronic LBP. Scientific research proved that among basic risk factors for the development of primary back pain, a significant number of physical (including industrial) and psychosocial factors was determined [12].…”
Section: проблемні теми Problematic Topicsmentioning
confidence: 99%